Education Agents and Their Work with Universities - Raimo, Vincenzo; Huang, Iona; West, Eddie (International Higher Education, 2021)
Education agents are a key feature of the ever more commercialized journey that thousands of international students make each year to enroll in universities abroad. They are intermediaries between universities, increasingly desperate for tuition fee revenues, and students searching for their perfect study destination. They have become a staple of the recruitment industry. But what are agents, and why do universities work with them? And what governance mechanisms exist to protect students from unscrupulous agents?